TEKNOLOGI, PERDAGANGAN INTERNASIONAL DAN PERTUMBUHAN EKONOMI: SUATU KAJIAN TEORI EKONOMI KLASIK KE PERDAGANGAN INTERNASIONAL MODERN - Sidik Budiono (Fakultas Bisnis UKDW, 2011)
There are 3 phenomens of most economic which undivided that openess and international trade and economic growth. Openess is the first frame for most country to do consolidation for its capability and weakness. International trade have able support high economic growthsignificantly. This paper would like to inform us about development of international economic from Classical Economic era to Modern International Economic (integration of endogenous growth and trade). The analyzis is not only comparative static approach but alsointertemporal approach. Scientificly the country’s advantage of modern international trade is not only analyzed for technology and specialization but also countries’s factor share. Generally, all countries tend to the long term equilibrium in the balance growth path.Therefore, each country and rest of the world will able to meet welfare economy not only individually but also international.Keywords: Technology, International Trade, Economic Growth, Balance Growth Path, Factor Share, Total Productivity, Bang-Bang Control.